Characteristics and Outcomes of In-Hospital Cardiac Arrest Events During the COVID-19 Pandemic: A Single-Center Experience From a New York City Public Hospital. Issue 11 (November 2020) - Miles, Jeremy A.; Mejia, Mateo; Rios, Saul; Sokol, Seth I.; Langston, Matthew; Hahn, Steven; Leiderman, Ephraim; Salgunan, Reka; Soghier, Israa; Gulani, Perminder; Joshi, Keval; Chung, Virginia; et al.
Abstract : Background: Patients hospitalized for severe coronavirus disease 2019 (COVID-19) infection are at risk for in-hospital cardiac arrest (IHCA). It is unknown whether certain characteristics of cardiac arrest care and outcomes of IHCAs during the COVID-19 pandemic differed compared with a pre-COVID-19 period. Methods: All patients who experienced an IHCA at our hospital from March 1, 2020 through May 15, 2020, during the peak of the COVID-19 pandemic, and those who had an IHCA from January 1, 2019 to December 31, 2019 were identified. All patient data were extracted from our hospital's Get With The Guidelines–Resuscitation registry, a prospective hospital-based archive of IHCA data. Baseline characteristics of patients, interventions, and overall outcomes of IHCAs during the COVID-19 pandemic were compared with IHCAs in 2019, before the COVID-19 pandemic. Results: There were 125 IHCAs during a 2.5-month period at our hospital during the peak of the COVID-19 pandemic compared with 117 IHCAs in all of 2019. IHCAs during the COVID-19 pandemic occurred more often on general medicine wards than in intensive care units (46% versus 33%; 19% versus 60% in 2019; P <0.001), were overall shorter in duration (median time of 11 minutes [8.5–26.5] versus 15 minutes [7.0–20.0], P =0.001), led to fewer endotracheal intubations (52% versus 85%, P <0.001), and had overall worse survival rates (3% versus 13%; P =0.007) compared with IHCAs before the COVID-19 pandemic. Conclusions: Patients who experienced an IHCA during the COVID-19 pandemic had overall worse survival compared with those who had an IHCA before the COVID-19 pandemic. Our findings highlight important differences between these 2 time periods. Further study is needed on cardiac arrest care in patients with COVID-19. Abstract : Supplemental Digital Content is available in the text.